Tekanan Koersif, Mimetic, Dan Respon Atas Perubahan Status Tata Kelola PTNBH Pada PTN X - Fathir Aulia Bufi; Suhanda Suhanda; Fauzan Misra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
There are three levels of PTN status, namely, Legal Entity PTN (PTN-BH), Public Service Agency PTN (PTN-BLU), and Work Unit PTN (PTN-Satker). The level is based on the level of autonomy in financial and resource management. The requirement for an autonomous university is to have certainty about good university governance or university governance. Governance means not only institutionally inscribed rules, but also the organization's responsiveness to whom and for what. This study analyzes why and how the implementation of governance practices in universities after the status of Legal Entity State Universities (PTNBH). Interview and observation techniques were used in this study to collect the required data. Technical thematic analysis is used to search for themes, themes that are in accordance with the research objectives. The process of adopting the idea of PTNBH in Higher Education is based on pressure, both coercive and mimetic. The low commitment of university leaders in the process of determining the idea of PTNBH resulted in a difference in understanding of the idea of PTNBH in the university environment. This reason resulted in decoupling, due to the low commitment of campus leaders in implementing policies substantially (Boxenbaum, 2017; Bromley, 2012). The existence of decoupling in the process of determining the idea of PTNBH has an impact on the ceremonial governance practices of PTNBH.